EXPERIENCES OF IMMIGRANT WOMEN ACCESSING HEALTH CARE IN PUNTA ARENAS, CHILE - Ojeda, Mackarena Alejandra Antilef; Santos, Evangelia Kotzias Atherino dos; Damiani, Pattrícia da Rosa (My University, 2020)
ABSTRACT Objective: to understand the experience of immigrant women on access to health care in the city of Punta Arenas, Chile. Method: a qualitative, exploratory, and descriptive approach study, in which 13 immigrant women took part. Data collection was carried out between March and July 2019, through four different focus groups. A thematic analysis was carried out. Results: from the analysis of the participants' narratives, the following categories emerged, detailed and analyzed in the light of other studies related to the theme: Use of the health services; Satisfaction in using the health services, and Obstacles to the use of the health services. Conclusion: in general, the immigrant population is required to know about their rights and duties as users of the health system.
Keywords: women; comprehensive health care; women's health services; emigrants and immigrants; migrant receiving society; nursing